AKTIVITAS KOMUNIKASI PEMASARAN PADA MEDIA ONLINE INSTAGRAM INSIDE LOMBOK DALAM MENINGKATKAN JUMLAH CLIENT : (STUDI PADA DIVISI MARKETING INSIDE LOMBOK) - Ni Putu Ayu Nanda Widyasuari; Eka Putri Paramita; Ida Ayu Sutarini (Program Studi Ilmu Komunikasi Universitas Mataram, 2023)
ABSTRACT In its empirical reality it is almost impossible to market without communication. Communication is always present in every marketing. The business world needs communication science to explain itself broadly. The existence of online media and determining what media will be used in conducting marketing communications is important, because it is through this media that every idea and idea can be conveyed. Online media is a form of convergence and digitalization of media today so that people are easier to get information. One of the fast-growing online media currently on the island of Lombok is Inside Lombok. To increase the number of Inside Lombok clients, the right marketing communication strategy is needed. This research is a qualitative descriptive research. The informants in this study consisted of key informants and additional informants. Data collection techniques are carried out through interviews, observation, and documentation. Meanwhile, the stage to test the validity of data uses the data sources triangulation technique. The result showed that the marketing communication activities carried out by Inside Lombok in increasing the number of clients by implementing an integrated marketing communication strategy in its planning, uploading content, client testimonials and data in the form of insight are Inside Lombok’s efforts to increase the number of clients. keywords : Marketing communication activities, inside lombok, increasing the number of clients.